Investigating the Related Factors in Developing the Status of Responding to Expectations in the Alishahr Comprehensive Health Services Center in 2018: A Qualitative Study - farzaneh Ghalegolab; ali khani jeihooni; Abbas Ghavam (Fasa University of Medical Sciences, 2020)
Background & Objective: Clients are at the heart of the health system and their satisfaction indicates the correctness of the services. Therefore, the purpose of this study was to determine the factors relevant to the development of the status of responding to expectations in Alishahr Comprehensive Health Services Center in 2018. Materials & Methods: The present study is qualitative in the form of directed content analysis.  Results: According to the respondents, the four components of response time, the factor of manpower in response, the management factor in response, the factor of equipment and facilities in responding to the respondents are the most important factors in the satisfaction of the respondents. Accordingly, the factor of speed, accuracy in doing client's affairs (90.9%) is the most important factor of time component; The factor of behavior with concerning clients, the responsiveness and responsibility for the client's business and having tolerance and a positive desire to deal with the client (90.1%) are the most important factors of manpower; Transparency and proper information and quality of service (quality of service) (86.4) The most important factor of the management component; Finally, the factors of cleanliness of the workplace (creating a pleasant and elegant environment) and the physical appearance of the staff, the heating and cooling system, the proper sanitary, adornment and health and safety of the work environment (77.3%) are the most important factors of the equipment component and facilities. Conclusion: Considering the results of this study that the provision of services in some cases is not optimal, it is suggested that by establishing a proper referral system and monitoring, it will increase the satisfaction of the clients.